Neurophysiological Analysis of Intermanual Transfer in Motor Learning - Oosawa, Ryuji; Iwasaki, Risa; Suzuki, Tomotaka; Tanabe, Shigeo; Sugawara, Kenichi (Frontiers in Human Neuroscience, 2019)
The purpose of this study was to examine the effect of motor training on motor imagery, by comparing motor performance and motor cortex excitability changes with and without intermanual transfer of motor learning. Intermanual transfer was investigated in terms of excitability changes in the motor cortex and motor performance from right hand training to left hand performance. Participants were assigned to a transfer training group and a control group. We recorded motor evoked potentials induced by transcranial magnetic stimulation, applied to the left extensor carpi radialis both with and without intermanual transfer. The results showed that after learning by the right hand, motor evoked potentials decreased during left hand motor imagery. Motor evoked potentials during motor imagery were significantly decreased by unilateral training in the transfer training group. Since intermanual transfer plays an important role in stabilizing performance by the contralateral side, this result suggests that unilateral training decreases motor evoked potentials during motor imagery on the contralateral side. In the control group, without right hand training, motor evoked potentials significantly increased after left hand training during motor imagery. In the trained side, we found increased excitability in the agonist muscle area of the primary motor cortex. However, in the untrained side, excitability decreased in the homonymous muscle area of the primary motor cortex. This constitutes an increase in inhibitory effects and suggests that excitability changes in the respective neural circuit contribute to skilled performance by the ipsilateral and contralateral sides in the same motor task.